Analisis Perencanaan Tingkat Pelayanan Fasilitas Pejalan Kaki Di Kawasan Tertib Lalu Lintas (Studi Kasus: Jalan Kombes Haji Umar) Kota Pagar Alam - Esti Nurmalasari; M.Sang Gumilar; Dyan Pratnamas (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2018)
Kombes haji umar Street is orderly traffic area in the city of Pagar Alam City. However on kombes haji umar street there are no pedestrian facilities. Because of this problem, there is an analysis of the level of pedestrian facilities. Data collection methods used in this research is the observation and questionnaire. Variable that has been obtained from the survey results directly in field obtained the highest pedestrian flow of 13 pedestrian/m/min, average speed of pedestrian 68.03 m/min, and a density of 0.191 pedestrian/m2. The volume of pedestrian on the road observation is of 23 pedestrians/mnt/m. Width design of pavement for pedestrians in the get from the average volume per minute at intervals of 15 minutes is 1.87 mon the right side and the left side of the road. Service levels on the need for pedestrian facilities in the way of initializing Haji Umar included in categories